Analisis Strategi Bauran Pemasaran Agenpos (Studi Pada Agenpos Kota Semarang) - Anshari, Dimas Irfan; Pradhanawati, Ari; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2016)
Agenpos as businesses need a strategy to support the sustainability of its business, including strategy Marketing Mix Service. In passage of time, effort there Agenpos that can get big turnover, there also has not been able to get it. The aim of this study is to knowing alternative strategies in developing Agenpos by using analysis of Marketing Mix Service. This research is a descriptive study with qualitative data support. Data collection techniques obtained through in-depth interviews, observation of the author as well as real data infield. Based Marketing Mix Agenpos big turnover obtained results (1) Locations is very strategic. (2) Rates obey PT. Pos Indonesia (3) The product is almost the same as Kantorpos (4) Promotion needs to improve (5) Employees maximum 2 people (6) The process was based on procedures (7) Physical Features Agenpos Sattar is good but needs to be improved. Based Marketing Mix Agenpos small turnover obtained results (1) the location is quite strategic. (2) Rates obey PT. Pos Indonesia. (3) The product is almost the same as the post office (4) Promotion needs to be improved (5) Employees maximum 3 people. (6) The process was based on procedures (7) physical appearance needs to be improved. Stimulus of Agenpos large turnover are (1) very strategic location (2) Cooperate with online shops. Obstacles are (1) a small room. (2) physical appearance needs to be improved. Stimulus of Agenpos small turnover are (1) Agenpos BKM Krida Asih Mukti cooperate with the locals. (2) Agenpos Kurniawan have social media accounts. Obstacles are (1) Limited location. (2) Physical appearance less. (3) Lacking of promotions. Conclusion that Agenpos strongly influenced by the location, cooperation with onlineshop, promotion to the community as well as their social media accounts. It is suggested to improve the physical appearance of the outside in, intensify promotion, formed a partnership with an online shop or surrounding communities